2005
DOI: 10.1038/sj.ijir.3901367
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction in women partners of men with erectile dysfunction

Abstract: We evaluated 113 female partners of men with erectile dysfunction (ED) attending a sexual dysfunction clinic in order to define sexual dysfunction among these women. In all, 51 (45%) women denied having any sexual dysfunction. The other 62 (55%) responded to questions classifying their complaint(s) according to the international classification of female sexual dysfunction (FSD) in the following topics (40/62, 65%, reported having more than one problem): decreased sexual desire (n ¼ 35, 56%), sexual aversion (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 14 publications
2
29
0
2
Order By: Relevance
“…[1][2][3][4][5][6][7][8] The majority of the women, whose partners were treated with PDE5i for 6 months, experienced improvements in their own sexual function, a finding that accords with earlier studies. 12 However, as reported in earlier papers, those that recorded lower levels of functioning on the FSFI were not necessarily dissatisfied with their partners' treatment.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8] The majority of the women, whose partners were treated with PDE5i for 6 months, experienced improvements in their own sexual function, a finding that accords with earlier studies. 12 However, as reported in earlier papers, those that recorded lower levels of functioning on the FSFI were not necessarily dissatisfied with their partners' treatment.…”
Section: Discussionsupporting
confidence: 80%
“…[1][2][3][4][5][6][7][8] Treatment of men with ED with oral phosphodiesterase type 5 inhibitors (PDE5i) has also been reported to have positive benefits for their female partners. [9][10][11][12] Most of these studies have relied on standardized sexual function (for example, Female Sexual Function Index (FSFI)) 13 and treatment satisfaction questionnaires.…”
Section: Introductionmentioning
confidence: 99%
“…When comparing to Greenstein et al 15 there would appear to be a difference in both the prevalence and pattern of the FSD in women of PE partners, where the highest rates of FSD are seen in the arousal sensation and orgasm categories, compared to partners of men with ED, where orgasm and desire are the largest categories of dysfunction. Riley and Riley 4 found that nearly two thirds of the women presenting with sexual desire disorder, who are also partners of men with PE, had a combination of impaired arousal and diminished orgasm attainment.…”
Section: Discussionmentioning
confidence: 64%
“…14 An investigation to assess the prevalence of FSD in female partners of men with ED attending a sexual dysfunction clinic found that 55% of the 113 women assessed reported some level of sexual dysfunction, with 35% reporting more than one sexual dysfunction. 15 The mostly commonly reported problems were difficulties with orgasm, and reduced sexual desire. Of course, these figures only represent the women and partners who agreed to take part in the study and there is no indication of the timing of the onset of the men's or women's sexual dysfunction and, therefore, no clarity as to which preceded or accompanied which.…”
Section: Introductionmentioning
confidence: 99%
“…As in men with ED, evaluation of the sexual function of the partner is also important in the diagnosis and prognosis of women with vaginismus. 20,21 The rate of men having a sexual problem was found to be 65.6% with DSM-IV-TR criteria and GRISS transformed subscale scores. Taking into account the fact that 56.2% of men had inadequate sexual knowledge and 50% had only an education level of elementary school, it can be inferred that the unawareness of having a sexual dysfunction in oneself can be associated with an inadequate education level.…”
Section: Discussionmentioning
confidence: 99%